Menangani Cabaran Wanita Melalui Kajian Wacana Hadis Nabawi: Addressing the Challenges of Women Through Discourse Study of Hadith Nabawi - Abdullah, Ariza; Abdul Jabar, Mohd Azidan; Mustapha, Nik Farhan; Toklubok@Hajimaming, Pabiyah (Perspektif Jurnal Sains Sosial dan Kemanusiaan, 2016)
<span style="display: inline !important; float: none; background-color: transparent; color: #000000; font-family: 'Helvetica Neue',Helvetica,Arial,sans-serif; font-size: 12px; font-style: normal; font-variant: normal; font-weight: 500; letter-spacing: normal; line-height: 13.2px; orphans: 2; text-align: left; text-decoration: none; text-indent: 0px; text-transform: none; -webkit-text-stroke-width: 0px; white-space: normal; word-spacing: 0px;">Women in this age of globalization faces many kinds of challenges intellectually and physically and need cooperation from the community and support of various institutions in order to bring about positive change in society itself. This paper aims to show the solution advocated by Islam through what is inherited through the Prophet Muhammad PBUH as a model through the language of the hadith narrated by his companions, especially the women themselves. The solution was not out-of-date and even able to bring changes, as it has changed women at the age of ignorance to become civilized woman and far advanced. This is because it is based on the methodology based on Al-Quran and Sunnah. This methodology becomes apparent when discovered through the social process contained in the passage of Hadith Nabawi. Therefore Fairclough’s Three Dimensional Conception Model (1992), which combines social analysis with textual analysis and discourse practices is used to prove the social practice of successful women who went through the current challenges and meet the principles of Islamic methodology concerning women outlined by al-Siba'i (1999). This is because social studies alone are not sufficient to achieve an even solution and the findings only account for the existence of problems and challenges of women. Resolution of the study of al-Moumani (2013), Umar (2011), and others call for the need to return to the example set by the Prophet Muhammad PBUH but did not provide a practical solution. Textual studies on the hadith can contribute to improving the social and familial institutions that trigger a variety of bad symptoms in addition to awaken the interest of the society towards language as social solutions. Thus empowering women in facing the challenges of globalization can bring transformation to the development of society and the state.